Pengaruh Rasio Kemandirian Keuangan Daerah dan Rasio Ketergantungan Fiskal Terhadap Indeks Pembangunan Manusia Pada Kabupaten dan Kota Provinsi Kalimantan Selatan Tahun 2014-2020 - Digdowiseiso, Kumba; Muhammad Bahtiar Satrio (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study is to determine the effect of the ratio of regional financial independence and the ratio of fiscal dependence on the human development index in South Kalimantan Province in 2014-2020. Sampling was carried out with saturated samples found in 13 districts and cities in South Kalimantan Province. This research method uses panel data regression method and Fixed Effect estimation model which was selected as the best estimator model. Data analysis of this study used the STATA/MP Version 16 computer program. The results of the study stated that the ratio of regional financial independence had a negative and significant effect on the Human Development Index. Fiscal dependency ratio has a negative and insignificant effect on the human development index